100‐year time series reveal little morphological change following impoundment and predator invasion in two Neotropical characids. (27th February 2019) - Geladi, Ilke; De León, Luis Fernando; Torchin, Mark E.; Hendry, Andrew P.; González, Rigoberto; Sharpe, Diana M.T.
Abstract: Human activities are dramatically altering ecosystems worldwide, often resulting in shifts in selection regimes. In response, natural populations sometimes undergo rapid phenotypic changes, which, if adaptive, can increase their probability of persistence. However, in many instances, populations fail to undergo any phenotypic change, which might indicate a variety of possibilities, including maladaptation. In freshwater ecosystems, the impoundment of rivers and the introduction of exotic species are among the leading threats to native fishes. We examined how the construction of the Panama Canal, which formed Lake Gatun, and the subsequent invasion of the predatory Cichla monoculus influenced the morphology of two native fishes: Astyanax ruberrimus and Roeboides spp. Using a 100‐year time series, we studied variation in overall body shape over time (before vs. after impoundment and invasion) as well as across space (between an invaded and an uninvaded reservoir). In addition, we examined variation in linear morphological traits associated with swim performance and predator detection/avoidance. Notwithstanding a few significant changes in particular traits in particular comparisons, we found only limited evidence for morphological change associated with these two stressors. Most observed changes were subtle, and tended to be site‐ and species‐specific. The lack of a strong morphological response to these stressors, coupled with dramatic population declines in both species, suggests they may be maladapted to the anthropogenically perturbed environment of Lake Gatun, but direct measures of fitness would be needed to test this. In general, our results suggest that morphological responses to anthropogenic disturbances can be very limited and, when they do occur, are often complex and context‐dependent.